Modelling the respiration rate of dabai fruit (Canarium odontophyllum Miq.) stored in different packaging films - Azhar Shapawi, Zahrah-Izati; Ariffin, Siti Hajar; Shamsudin, Rosnah; Mohammed Amin Tawakkal, Intan Syafinaz; Mohd Basri, Mohd Salahuddin (Universiti Putra Malaysia, 2023)
Dabai (Canarium odontophyllum Miq.) is a highly nutritious fruit that has a huge potential to be marketed both locally and globally. However, the lack of promotion leads to an oversupply during peak season, thus reducing its market price. Proper handling and packaging are therefore necessary to maintain the quality and extend the shelf life of dabai. In the present work, nylon film with an oxygen transmission rate (OTR) of 55 cc/m2 /day and water vapour transmission rate (WVTR) of 334 g/m2 /day; polyethylene terephthalate (PET) film with an OTR of 90 cc/m2 /day and WVTR of 35 g/m2 /day; and low-density polyethylene (LDPE) film with an OTR of 8000 cc/m2 /day and WVTR of 200 g/m2 /day were used to pack dabai and stored at 5°C for 14 d. All films had a dimension of 200 × 300 mm, and a thickness of 0.01 μm. It was found that dabai maintained its hue angle (h°) values within the dark purple region (299.73° to 338.64°) and its lightness (L*) values throughout storage. However, the colour intensity (chroma) significantly changed (p < 0.05) between different films throughout storage (p < 0.05). The control sample had the most significant decrease in firmness and weight (p < 0.05) between day 0 and 14, followed by the samples stored in PET, LDPE, and nylon. Whereas the samples in LDPE demonstrated the lowest respiration rate as compared to nylon and PET. The uncompetitive Michaelis-Menten equation model was used to model the respiration rate of dabai. Results showed that all films obtained good fit (R 2 of near to 1). Additionally, the mean relative percentage (E) was less than 10, thus indicating that the data were suitable for real-time application.